2017
DOI: 10.1080/0284186x.2017.1285498
|View full text |Cite
|
Sign up to set email alerts
|

Functional image-guided dose escalation in gliomas using of state-of-the-art photon vs. proton therapy

Abstract: Dose escalation can be achieved with IMRT, VMAT and IMPT while respecting normal tissue constraints, yet with IMPT being most favorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
(32 reference statements)
2
7
0
Order By: Relevance
“…From a clinical toxicity standpoint, reporting of differences in PTV instead of GTV is a more clinically meaningful interpretation of observed differences. This was consistent with prior reports of similar studies utilizing 18 F-Fluoro-ethyl-tyrosine (FET) based RT contouring [13][14][15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…From a clinical toxicity standpoint, reporting of differences in PTV instead of GTV is a more clinically meaningful interpretation of observed differences. This was consistent with prior reports of similar studies utilizing 18 F-Fluoro-ethyl-tyrosine (FET) based RT contouring [13][14][15].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, by using volumetric-modulated arc therapy with simultaneous integrated boost planned with similar planning constraints and arc arrangements, we were able to demonstrate that treatment of the additional target volume suggested by 18 F-DOPA PET biologic imaging did not result in increased doses to OAR. This was consistent with a recent study evaluating VMAT plans, standard intensity-modulated RT, and spot-scanning proton RT [15]. In this report, all techniques spared OAR with FET-PET guided dose-escalation, although protons resulted in the greatest sparing.…”
Section: Discussionsupporting
confidence: 91%
“…[3] Since the “4π radiotherapy” solution is commercially available, it is used by several researchers in their planning studies. [23456789101112131415] The studies include sites such as thorax (lung stereotaxy),[2371215] brain,[1213141516] head and neck,[510] abdomen (liver stereotactic body radiotherapy),[71115] pelvis (prostate),[9] and phantom[6] in knowledge-based planning[17] besides several other discussions in scientific forums. [812] As claimed by Dong et al , in 2013, they have achieved a 4π c (steradian) solid angle at the tumor center for thorax cases and subsequently similar claims were made by rest of the authors until the last month (June 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[812] As claimed by Dong et al , in 2013, they have achieved a 4π c (steradian) solid angle at the tumor center for thorax cases and subsequently similar claims were made by rest of the authors until the last month (June 2019). [234567891011121314151718] However, the question “whether it is possible to obtain a 4π c solid angle using a linear accelerator in three-dimensional Euclidean space?” is an interesting one to probe into against the backdrop of these mushrooming scientific literature and commercial products. The simple answer is “no”.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that more work has to be done with 18F-HX4 PET before radiobiologically optimized hypoxia planning with e.g., dose painting [32,33] is clinically applicable. In the current study by Holm et al [34], dose painting of PET-positive tumor regions was explored in silico for glioma patients. 18F-fluoro-ethyl-tyrosine (FET) PET for target definition and risk-adapted treatment planning with X-rays (IMRT/volumetric modulated arc therapy, VMAT) or protons was employed.…”
mentioning
confidence: 99%